EFFECT OF IMPLEMENTATION OF BELIEF SYSTEM AND INTERACTIVE CONTROL SYSTEM ON ECONOMIC PERFORMANCE WITH ENVIRONMENT PERFORMANCE AS MODERATOR - Tauperta Siregar (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
The purpose of this study was to determine whether there is an influence of the application of belief systems and interactive control systems on economic performance with environmental performance as a moderating factor. This research was conducted at companies engaged in mining and oil and gas and registered as participants in the PROPER for the last 10 years. The independent variables of this research are belief system and interactive control system. The dependent variable of this study is economic performance. Supporting variables (moderating) are environmental performance. The population in this study are mining and oil and gas companies. Sampling technique using a purposive sampling method. This method requires taking the number of samples as much as determined by researchers as a target that must be met. The sample in this study were 12 companies. The data collection method uses the questionnaire method. Testing data in this study uses a validity test, reliability test, normality test, heteroscedasticity test, autocorrelation test, multicollinearity test, and linear regression test. Data processing is performed using statistical package statistical application (SPSS) version 25. The results of this study indicate that belief systems on economic performance have a negative significant relationship to economic performance, interactive control systems have a positive and not significant relationship to economic performance, environmental performance has a significant positive relationship to economic performance, environmental performance is not able to moderate the influence of belief systems on economic performance, and environmental performance is able to moderate the effect of interactive control systems on environmental performance.